Pilihan Bahasa Dalam Komunikasi Mahasiswa Multietnik Pbsi Serta Implikasinya Terhadap Pembelajaran Berbicara Pada Siswa Sma - Ayu Natalia; Lazarus Linarto; Petrus Poerwadi; Albertus Purwaka; Misnawati Misnawati (Universitas Palangka Raya, 2023)
This study aims to describe the choice of language in the communication of PBSI muktiethnic students which include: (1) when doing lecture assignments, (2) during HMPS activities, (3) when chatting in the campus canteen, and (4) the implications for learning to speak in senior high school. The results of research on the choice of language in PBSI multi-technical student communication show (1) the choice of language when doing coursework is in the form of: a. Dayak Ngaju speakers and Batak speakers choose Indonesian; b. Dayak Ngaju speakers and Banjar speakers choose Indonesian and Banjar languages; c. Ma'anyan speakers and Ma'anyan speakers choose Indonesian, Ma'anyan and Banjar; d. speakers of Javanese, bMaanyan and Dayak Ngaju languages choose Indonesian and Dayak Ngaju languages; and e. speakers of Ma'anyan, Banjar and Batak languages choose Indonesian and Banjar languages. (2) the choice of language during HMPS activities is in the form of: a. speakers of Dayak Ngaju and Banjar languages choose Indonesian; b. speakers of Javanese and Batak languages prefer Indonesian and Banjar languages; c. speakers of Ma'anyan, Banjar and Dayak Ngaju languages choose Indonesian. (3) the choice of language when chatting in the campus cafeteria is in the form of: a. speakers of Dayak Ngaju and Dayak Ngaju languages choose Indonesian and Dayak Ngaju languages; b. speakers of Banjar and Dayak Ngaju languages choose Indonesian and Banjar languages; and c. speakers of Ma'anyan, Batak and Dayak Ngaju languages choose Indonesian and Banjar languages. As well as (4) the implications for learning to speak in high school, especially in K.D 4.19 which is related to material things that must be prepared before staging a drama, namely dialogue between characters..